2005
DOI: 10.1002/ffj.1503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile aroma compounds of strawberry wine using solid-phase microextraction techniques coupled with gas chromatography–mass spectrometry

Abstract: Aroma compounds of strawberry wine were trapped by both headspace (HS) and immersion (IM) solidphase microextraction (SPME). In the strawberry wine, esters were found to be the major compounds detected by both techniques. When using the HS-SPME technique, eight ester compounds (ethyl hexanoate, ethyl octanoate, octyl acetate, methyl decanoate, ethyl-9-decanoate, ethyl decanoate, ethyl cinnamate and ethyl dodecanoate), and (E)-nerolidol could be identified. Seven esters (amyl acetate, ethyl hexanoate, hexyl ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 23 publications
0
46
1
Order By: Relevance
“…Since the extraction efficiency of red wine aroma compounds by HS-SPME strongly depends on their polarity, their affinity to the fibre-coated phases, the temperature and time on the equilibrium (De la Calle García et al, 1998;Baptista et al, 2001), it is probable that, in the results reported in this paper, interactions between phenol and volatile compounds were not significant enough to be measured by SPME fibre. The PDMS fibre used in this study is considered by many authors as the most suitable for adsorbing volatile compounds from wines and other alcoholic beverages (Kafkas et al, 2006). Dietz and co-workers (2006) stated that, in general, a wide range of possible solutions exist for a given analytical problem in SPME.…”
Section: Effect Of Polyphenols On Aroma Perception Of Winementioning
confidence: 99%
“…Since the extraction efficiency of red wine aroma compounds by HS-SPME strongly depends on their polarity, their affinity to the fibre-coated phases, the temperature and time on the equilibrium (De la Calle García et al, 1998;Baptista et al, 2001), it is probable that, in the results reported in this paper, interactions between phenol and volatile compounds were not significant enough to be measured by SPME fibre. The PDMS fibre used in this study is considered by many authors as the most suitable for adsorbing volatile compounds from wines and other alcoholic beverages (Kafkas et al, 2006). Dietz and co-workers (2006) stated that, in general, a wide range of possible solutions exist for a given analytical problem in SPME.…”
Section: Effect Of Polyphenols On Aroma Perception Of Winementioning
confidence: 99%
“…The variability of yeast strains in their ability to produce volatile compounds has also been studied using SPME (MAURIELLO et al, 2009). SPME has also been applied to volatile organic compounds analysis in beer and wines (KAFKAS et al, 2005;SALINAS et al, 2004;MALLUCHOS et al, 2002).…”
Section: Head Space Solid Phase Micro-extraction (Spme -Hs)mentioning
confidence: 99%
“…Changes in growth conditions influence their metabolisms, resulting in altering VOC patterns (Wheatley et al 1997. For example during spirits production with carbohydrate-rich substrates such as potato or wheat, the yeast Saccharomyces cerevisiae produces ethanol as main product, but the individual substrate provides different and characteristic aroma, caused by the minor components of the yeast and also the substrate (Conner et al 1998, Pinheiro et al 2001, Kafkas et al 2006, Porto et al 2006.…”
Section: Impact Of Substrate On Vocs Released By Fungimentioning
confidence: 99%